1995
DOI: 10.2166/wst.1995.0579
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of silver ions and hydrogen peroxide in the inactivation of E. coli: a preliminary evaluation of a new long acting residual drinking water disinfectant

Abstract: The inactivation efficiencies of silver ions, hydrogen peroxide and their combination was studied as part of a performance evaluation of the combined disinfectant for drinking water applications. The major advantages of such combined disinfectant include, low toxicity of its components, long lasting residual effect and low disinfection by product formation. Specific strains of E. coli (E. coli-B (SR-9) and E. coli K-12) were used in this study as target microorganisms and the separate and combined inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 0 publications
1
35
1
4
Order By: Relevance
“…Furthermore, the high bactericidal activity in neutral condition suggested that this catalyst is a very potential material to apply in drinking water disinfection. Ag + ions do elute from the catalyst surface, but the amount is no more than 0.09 mg/L in 1 h, and the World Health Organization (WHO) declared that silver does not cause adverse health effects and set a secondary maximum concentration level (MCL) of 90 lg/L [19,27,36]. Therefore, silver loaded on alumina was thought not only to increase the effectiveness of this catalyst system but also to be safe and economical, since the catalyst could be used several times after regeneration.…”
Section: Effect Of Ph Valuementioning
confidence: 99%
“…Furthermore, the high bactericidal activity in neutral condition suggested that this catalyst is a very potential material to apply in drinking water disinfection. Ag + ions do elute from the catalyst surface, but the amount is no more than 0.09 mg/L in 1 h, and the World Health Organization (WHO) declared that silver does not cause adverse health effects and set a secondary maximum concentration level (MCL) of 90 lg/L [19,27,36]. Therefore, silver loaded on alumina was thought not only to increase the effectiveness of this catalyst system but also to be safe and economical, since the catalyst could be used several times after regeneration.…”
Section: Effect Of Ph Valuementioning
confidence: 99%
“…Thus, exposure to silver ions damages multiple components of bacterial cell metabolism, including the permeability of the cell membrane, which leads to gross cellular structural changes, blockage of transport processes, and interference in the activity of vital enzymatic systems such as the respiratory cytochromes, alteration of proteins, and binding to DNA and RNA, which in turn affects their functionality. [6,17] Whereas combinations of cationic silver with other biocides such as silver sulfadiazine with or without chlorhexidine digluconate, [23] copper, [24] and hydrogen peroxide [25] are well known and used, [9,11] the use of metallic silver in biocidal combinations has been limited to the coating or impregnating of biocidal polymers with silver [26] or to the mixing of antibiotics with silver. [27] All of these combinations displayed synergistic activity.…”
Section: Introductionmentioning
confidence: 99%
“…4). Полученные нами результаты согласовываются с данными зарубежных и отечественных исследователей (Shahverdy, 2007, Pedahzur, 1995, которые отмечают, что серебро стимулирует иммунитет, стабилизирует обмен веществ в организме и обезвреживает бактерии, вирусы и грибки, оставаясь относительно толерантным к симбиотической микрофлоре (Hidaka, 2005). Благодаря новейшим технологиям эти свойства серебра могут быть многократно усиленны за счет особенностей влияния наночастиц на различные биологические объекты (Roberfroid et al 1995).…”
Section: а бunclassified